Ameliorative effect of biosynthesized titanium dioxide nanoparticles using garlic extract on the body weight and developmental toxicity of liver in albino rats compared with chemically synthesized nanoparticles - Kamal, Zeinab; Ebnalwaled, A. A.; Al-Amgad, Zeinab; Said, Alaa H.; Metwally, Asmaa A.; Zigo, František; Ondrašovičová, Silvia; Rehan, Ibrahim F. (Frontiers in Veterinary Science, 2022)
The application of metallic nanoparticles results in subsequent risks to human and animal health. Titanium dioxide nanoparticles (TiO2NPs) are the most commonly synthesized metallic oxides in the world. Exposure to TiO2NPs can induce toxicity in the target organisms. This study aimed to evaluate the effect of green and chemical TiO2NPs on maternal and embryo-fetal livers. Green TiO2NPs using garlic extract (GTiO2NPs) and chemical TiO2NPs (CHTiO2NPs) were synthesized and characterized by X-ray powder diffraction and high-resolution transmission electron microscopy. The cytotoxicity of both chemical and green TiO2NPs was determined against HepG2 cell lines. Fifty pregnant female Albino rats were equally and randomly divided into five groups. Group 1 was kept as a control. Groups 2 and 3 were orally treated with 100 and 300 mg/kg body weight of CHTiO2NPs, respectively. Groups 4 and 5 were orally treated with 100 and 300 mg/kg of GTiO2NPs, respectively, daily beginning on day 6th to day-19th of gestation. All dams were euthanized on gestation day 20. All live fetuses were weighed and euthanized. Blood and tissue samples were collected for biochemical, histopathological, and Bax-immunohistochemical expression analyses. Our results indicated that garlic can be used as a reducing agent for the synthesis of TiO2NPs and the produced NPs have no toxic effect against HepG2 cells compared with CHTiO2NPs. The mean serum level of AST, ALT activity, and total protein level significantly increased when TiO2NPs were administered at high doses. Histologically, the CHTiO2NPs-treated groups revealed vacuolated and necrotized hepatocytes, with congested and dilated blood vessels in the fetal and maternal liver. The immunohistochemistry revealed distinct positive staining of Bax expressed in the hepatocytes. Nevertheless, biosynthesis of TiO2NPs using garlic extract has minimal effect on the normal architecture of the liver. It could be concluded that the bioactivity of TiO2NPs can be modified with green synthesis using garlic extract. Compared to the CHTiO2NPs, the exposure to GTiO2NPs showed a reduced degree of liver damage in maternal and embryo-fetal rats.